The globular cluster system of NGC 1399. I. A wide-field photometric study - Dirsch, B. (2003)
We present a photometric investigation of the globular cluster population of NGC 1399, the central galaxy in the Fornax cluster, in Washington C and Kron R filters within a field of 36′ × 36′, corresponding to about 200 × 200 kpc at the Fornax distance. This is the largest area around this galaxy ever studied with CCD photometry. The cluster system of NGC 1399 is found to extend farther than 100 kpc away from the galaxy. The color distribution exhibits a pronounced bimodality. Within a radial distance of about 55 kpc, the red clusters are more strongly concentrated toward the center than the blue clusters. At larger radii, the surface density profiles of the clusters are indistinguishable and match well the distribution of the galaxy light. Over the entire radial distance range, the surface brightness profile of NGC 1399 can be very well fitted by a power law with an exponent of -1.85 and a core radius of 3″.3. No steepening of the luminosity profile can be detected at large radii. We suggest that the power-law profile of NGC 1399 results from the galaxy being embedded in a large dark matter halo, which prevents the stellar density profile from steepening outward. The cluster system contains 6450 ± 700 clusters and the specific frequency is found to be 5.1 ± 1.2 in the V band. While NGC 1399 shows a pronounced color gradient the nearby comparison galaxy NGC 1404 does not show such a gradient. Using simple assumptions about the underlying population that formed during the same star formation event as the globular clusters, we present a model in which we use radially changing local specific frequencies for the red and blue subpopulations to fit the observations. We find that within 7′ the required specific frequency of the blue clusters alone is a factor of approximately 3 larger than that of the red ones. Outside this radius, however, both populations have the same high local specific frequency of around 8 and 13 (blue and red clusters, respectively).